The Prospects for Economic Growth in a Finite World. - SMITH, PETER (Quadrant Magazine, 2014)
The article reports on the essence of capitalism in a finite world. Topics discussed include connection between capitalism and the economic growth, impact of finiteness of resources on environmentalists, and obstruction in economic development of the world due to nuclear power projects and fracking.